Missing‐linker Defects in Covalent Organic Framework Membranes for Efficient CO2 Separation. Issue 41 (1st September 2022) - Guo, Zheyuan; Wu, Hong; Chen, Yu; Zhu, Shiyi; Jiang, Haifei; Song, Shuqing; Ren, Yanxiong; Wang, Yuhan; Liang, Xu; He, Guangwei; Li, Yonghong; Jiang, Zhongyi
Abstract: Covalent organic framework (COF) membranes with tunable ordered channels and free organic groups hold great promise in molecular separations owing to the synergy of physical and chemical microenvironments. Herein, we develop a defect engineering strategy to fabricate COF membranes for efficient CO2 separation. Abundant amino groups are in situ generated on the COF nanosheets arising from the missing‐linker defects during the reactive assembly of amine monomer and mixed aldehyde monomers. The COF nanosheets are assembled to fabricate COF membranes. Amino groups, as the CO2 facilitated transport carriers, along with ordered channels endow COF membrane with high CO2 permeances exceeding 300 GPU and excellent separation selectivity of 80 for CO2 /N2, and 54 for CO2 /CH4 mixed gas under humidified state. Our defect engineering strategy offers a facile approach to generating free organic functional groups in COF membranes and other organic framework membranes for diverse chemical separations. Abstract : The defect engineering strategy is developed for the bottom‐up fabrication of facilitated transport covalent organic framework membranes with missing‐linker defects for efficient CO2 separation.